Hematologic Chaos in Lupus Flare: A Case of Fulminant and Simultaneous Antiphospholipid, Anti-ADAMTS13, and Red Blood Cell Autoantibodies - Jafar Al-Mondhiry; Caroline Y. Chen; Michael H. Rosove (Case Reports in Rheumatology)
Systemic lupus erythematosus may present with several distinct autoimmune phenomena simultaneously. We report a patient presenting with three serious hematologic disorders: thrombotic thrombocytopenic purpura, catastrophic antiphospholipid syndrome, and warm-type IgG red cell autoantibodies. The case is an example of the complex clinical nature of lupus and the importance of accurately identifying individual complications in order to optimize management.